Effects of current density on size and surface morphology of high speed direct nano-crystalline nickel plating on titanium surface - Zaimah N.; Nurain A.; Hussain S. (Asian Research Publishing Network, 2023)
Electroplating known as "electrodeposition" is a method of producing a coating, usually metallic, on a surface by applying electric current. In this research work, electrolyte Ni was deposited on Ti by high speed electroplating directly without any pre-cleaning/pre-treatment with varied applied current density. This study reports the effects of deposition of Ni on Ti and it was found that the plating thickness increased with higher current densities, also fine grained structures obtained as the current density increased. Hardness of the deposits decreased as the current density is increased. These showed that the current density affects the coating thickness of Ni-Ti alloy coatings. High speed electroplating is electroplating on metal without any pretreatment process and eliminating oxide layer at high current density which result in high deposition rate of cation on cathode surface. 2006-2015 Asian Research Publishing Network (ARPN).